2018
DOI: 10.1172/jci.insight.123072
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase inhibits reactive adipogenesis and inflammation of colon and skin

Abstract: Conflict of interest: RDP is an employee of Halozyme Therapeutics Inc. RLG is a consultant for and has equity interest in Senté and MatriSys Bioscience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…A persistence of highmolecular weight HA enables this adipogenic response and results in much greater expression of Camp in the dermis at the site of infection. We have previously shown that increased hyaluronidase-1 activity (in contrast with the loss of hyaluronidase activity seen here in Cemip À/À mice) will inhibit reactive adipogenesis and Camp expression (Dokoshi et al, 2018). Our findings described in Figures 2 and 3 show that loss of Cemip enables the skin to respond to S. aureus infection by increasing expression of Camp, expanding DWAT and enhancing gene expression associated with adipogenesis.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A persistence of highmolecular weight HA enables this adipogenic response and results in much greater expression of Camp in the dermis at the site of infection. We have previously shown that increased hyaluronidase-1 activity (in contrast with the loss of hyaluronidase activity seen here in Cemip À/À mice) will inhibit reactive adipogenesis and Camp expression (Dokoshi et al, 2018). Our findings described in Figures 2 and 3 show that loss of Cemip enables the skin to respond to S. aureus infection by increasing expression of Camp, expanding DWAT and enhancing gene expression associated with adipogenesis.…”
Section: Discussionmentioning
confidence: 49%
“…We have recently shown that a major source of cathelicidin expression in the skin comes from the local differentiation of preadipocyte fibroblasts into adipocytes, a process we refer to as reactive adipogenesis (Zhang et al, 2015). Degradation of HA inhibits the capacity of preadipocytes to differentiate into mature adipocytes (Dokoshi et al, 2018;Ji et al, 2014). Therefore, we hypothesized that the digestion of HA by Cemip may inhibit the local adipogenic response and thus suppress the expression of the antimicrobial peptide by these cells.…”
Section: Loss Of Cemip Enhances Reactive Adipogenesismentioning
confidence: 99%
“…Adipose tissue undergoes local expansion after cutaneous tissue injury, inflammation, and bacterial infection in a phenomenon that we have named reactive adipogenesis (Dokoshi et al, 2018;Zhang et al, 2015). This phenomenon has been observed in other species.…”
Section: Reactive Adipogenesis: How the Adipogenic Response Defends Amentioning
confidence: 79%
“…Oral dextran sulfate sodium can be administered to induce acute colitis in mice, which results from increased epithelial wall permeability, impaired mucus secretion, dysregulated defensin production, and increased bacterial burden (Kruis et al, 2013). Recently, Dokoshi et al (2018) showed that these mice concomitantly developed increased mesenteric fat, submucosal layer thickening, mature adipocyte accumulation, and up-regulation of adipogenic genes, including Pref1 and Zfp423. Histologic examination of tissue from patients with inflammatory bowel disease showed similarly increased Pref1 expression and staining, suggesting that reactive adipogenesis occurs in both mouse and human colitis (Dokoshi et al, 2018).…”
Section: Reactive Adipogenesis: How the Adipogenic Response Defends Amentioning
confidence: 99%
“…The protective role of cathelicidin was also confirmed in survival analysis between Cnlp wild-type and knockout group. Consistently, human cathelicidin protects rats against sepsis after bacterial challenge [33] and the increased expression of cathelicidin in adipocytes surrounding the colon limits the release of bacteria from mice with experimental colitis [34]. Nevertheless, contradictory evidence also exists in the literature.…”
Section: Discussionmentioning
confidence: 99%